Circulation et transnationalisation de dispositifs et de catégories socio-politiques. Les « transitions vers la démocratie » et la « disparition forcée » au Chili et en Espagne - Paola Diaz (Les Cahiers de Framespa)
In this text we describe the circulation and transnationalization of socio-political apparatus between Spain and Chile. We focus on two post-authoritarian figures present in these two countries : "transitions to democracy," as an apparatus of post-authoritarian rule, and "forced disappearance," as a transnationalizated category of victimhood. If the apparatus "transitions to democracy" was circulated from Spain to Latin America –among political elites– than the category of "forced disappearance" began being circulated among non-governmental organizations and associations of families of the “disappeared” (desaparecidos) in Latin America, by which it came into transnational use and was mobilized in Spain beginning in 2000. In order to study these phenomena of circulation, this analysis focuses on the social and cultural operations of translating the historical and situated experience in apparatus and categories have acquired a certain abstraction away from their context of emergence.